Systematic Literature Review: Identifikasi Kesalahan Siswa Sekolah Menengah Pertama pada Materi Bilangan Bulat - Dame Enjelina Sigalingging; Indriyani Fransiska Tinambunan; Marianche Ferbina Tarigan; Natalia Susi Susanti Silitonga; Sola Gracia Manik (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study analyzes junior high school students' errors in solving mathematics problems involving integers. This study was conducted through a systematic literature review of 12 related research articles published between 2021 and 2026. The analysis shows that students' errors in integers include contextual, procedural, and technical (calculation) errors. The most common conceptualization errors were found in the understanding of positive and negative signs and the rules for mixed operations. The main causes of errors are a lack of in-depth conceptual understanding, the habit of memorizing without understanding, and a lack of practice using concrete media. Internal factors such as learning motivation and external factors such as learning methods and media also contribute. This study recommends that the mathematics learning process emphasize meaningful conceptual understanding, the use of concrete media, and learning strategies that engage students' mathematical connection skills. Thus, difficulties in learning integers can be minimized sustainably.